Evaluation on the Application of Stratified Double Net Cages for Freshwater Fish Aquaculture: Macrobenthic Assemblages as Bioindicator - P. Putro, Sapto; Sudaryono, Agung; Widowati, Widowati; Suhartana, Suhartana (Indonesian Aquaculture Society (MAI), 2014)
Various designs of floating fish cages have been developed by the fishermen, both for applications on the rivers, reservoirs, coastal areas, offshore and lakes. In order to optimise the ecological use of Lake Rawapening as fish farming area, it is necessary to change the design of cages as well as farming practice. The development of design of floating net cage has been done using Stratified Double Net Cages (SDNC), and it is considered to be one of the best alternatives to solve the problem. The aims of this study were to evaluate the application of Stratified Double Net Cages (SDNC) based on macrobenthic assemblages to assess the potential environmental impact caused by farming activities using SDNC. The results were compared to the reference areas, which were 1 (one) km away from the farming zones.This study was carried out at the ficinity areas of two SDNC. The cages were operated by fisherman groups of Ngudi Makmur and Rukun Santosa, located on the water column of Lake Rawapening, close to Asinan District, Central Java. The results showed that the composition of species macrobenthic assemblages between farming sites and control sites were different both in number and compotition, indicating the initial stage of disturbance caused by organic enrichment due to farming actitivites. The study provides important implications for the arrangement of Stratified Double Net Cage (SDNC) activities at Lake Rawapening, both in density and ordinate position in order to maintain the ecological function of this lake.